DIAGNOSTIC ACCURACY OF DIFFUSION-WEIGHTED IMAGING IN POSTERIOR FOSSA TUMOR - Bikram Jeet Singh; R. P. Bansal; Feroz Shaheen (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Infratentorial intra-axial tumors in the cerebellum and brainstem differ between pediatric and adult populations. While MRI is essential for diagnosing posterior fossa tumors, its ability to differentiate tumor types and grades is limited. Diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) measurements offer additional insights into tumor cellularity and malignancy potential.Objective: This study aims to evaluate the diagnostic accuracy of DWI and ADC values in differentiating posterior fossa tumors in pediatric and adult patients.Methods: Conducted at the Department of Radiodiagnosis and Imaging, Sher I Kashmir Institute of Medical Sciences, Soura Srinagar, this study involved 68 patients (22 pediatric, 46 adult). MRI, including DWI, was performed, and ADC values were measured using region-of-interest (ROI) placement. Data were analyzed using SPSS, with statistical significance set at p ≤ 0.05.Results: Pediatric tumors included pilocytic astrocytomas, ependymomas, medulloblastomas, and brainstem gliomas, while adult tumors comprised metastases, meningiomas, hemangioblastomas, schwannomas, and cystic lesions. Medulloblastomas exhibited lower ADC values due to high cellularity, while pilocytic astrocytomas showed higher ADC values. In adults, ADC values effectively differentiated metastases, meningiomas, hemangioblastomas, and schwannomas.Conclusion: DWI and ADC mapping provide valuable diagnostic insights for posterior fossa tumors, aiding in differentiation between tumor types. However, they should be integrated with conventional MRI and histopathological analysis for comprehensive tumor characterization. Further studies with larger cohorts and advanced imaging techniques may enhance diagnostic precision.